2024
DOI: 10.1038/s41550-024-02237-4
|View full text |Cite
|
Sign up to set email alerts
|

JWST detection of a supernova associated with GRB 221009A without an r-process signature

Peter K. Blanchard,
V. Ashley Villar,
Ryan Chornock
et al.

Abstract: Identifying the sites of r-process nucleosynthesis, a primary mechanism of heavy element production, is a key goal of astrophysics. The discovery of the brightest gamma-ray burst (GRB) to date, GRB 221009A, presented an opportunity to spectroscopically test the idea that r-process elements are produced following the collapse of rapidly rotating massive stars. Here we present James Webb Space Telescope observations of GRB 221009A obtained +168 and +170 rest-frame days after the gamma-ray trigger, and demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…We therefore tried to describe the multiband light curves with a single-decline-rate power law, f (t) ∝ t −1.56 ; the result is shown in Figure 1, where one can see that in all bands, there is no significant bump signature. Table 3 compares the parameters with the results reported by other works (Fulton et al 2023;Srinivasaragavan et al 2023;Blanchard et al 2024) and the general value of GRB-SNe (Cano et al 2017). Our results are close to those of Srinivasaragavan et al (2023) and consistent with the average value inferred by Cano et al (2017) for other GRB-SNe except for the expansion velocity of the ejecta, v ej .…”
Section: Light-curve Fitting and Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…We therefore tried to describe the multiband light curves with a single-decline-rate power law, f (t) ∝ t −1.56 ; the result is shown in Figure 1, where one can see that in all bands, there is no significant bump signature. Table 3 compares the parameters with the results reported by other works (Fulton et al 2023;Srinivasaragavan et al 2023;Blanchard et al 2024) and the general value of GRB-SNe (Cano et al 2017). Our results are close to those of Srinivasaragavan et al (2023) and consistent with the average value inferred by Cano et al (2017) for other GRB-SNe except for the expansion velocity of the ejecta, v ej .…”
Section: Light-curve Fitting and Resultssupporting
confidence: 88%
“…The close match with SNe Ic-BL in particular demonstrates the presence of a typical GRB-SN in the spectrum. These observations provide the first clear detection of an SN associated with GRB 221009A (Blanchard et al 2024). Moreover, Srinivasaragavan et al (2023) also announced that they found moderate evidence for the presence of an additional component arising from an associated SN and found that it must be substantially fainter than SN 1998bw (see more details in the review by Srinivasaragavan et al 2023).…”
Section: Conclusion and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The connections between GRBs and Supernovae have been documented several times. The cosmological distances of GRBs made the observations of the related SN very difficult because they can be immersed in the GRB optical afterglow, but some well-documented cases exist [16].…”
Section: Fitting the 1054 Event With A Grbmentioning
confidence: 99%
“…The connections between GRB and Supernovae have been documented several times. The cosmological distances of GRB made the observations of the related SN every difficult, because they can be immersed in the GRB optical afterglow, but some well documented cases exist [17].…”
Section: Fitting the 1054 Event With A Grbmentioning
confidence: 99%